CHARACTER ACCENTUATIONS RESEARCH OF BULLING PARTICIPANTS IN THE COTINGENT OF ADOLESCENTS OF A REGIONAL SOCIAL ESTABLISHMENT FOR MINORS - Ponomaryov, V.I. (World of Medicine and Biology, 2013)
The results of character accentuations research in bulling participants in the contingent of adolescents of a regional social establishment for minors showed that all the adolescents who participated in bulling had premorbid character burden in form of evidently expressed character accentuations, mainly of asthenic-and-neurotic type in bulling victims and hyperthymic-and-explosive and epileptoid type in bullers. It is elicited significant influence of organic factor in formation of character accentuation in adolescents who realize specific violence in the form of bulling in children and adolescents environment.
Keywords: bulling; adolescents; character accentuations